Determination of major antinutritional factors in Pennisetum glaucum L. and their relationship with protein and content yield (Bangladesh Journal of Botany, 2020)
Twenty pearl millet genotypes were used to explore and evaluate the diversity of antinutritional factors along with establishing their relationship with protein content and yield that contributes to its quality and farmers interest, respectively. A wide variation was observed for each of antrinutritional factors along with protein (7.54 - 11.94%) and yield (19.67 - 27.6 g/plant). The genotype HBL-0825-1 identified for having highest phenol, phytic acid and C-glycosylflavone content while genotype 78/711 for lowest Cglycosylflavone and phytic acid content along with maximum protein content. HBL-72 was identified for having maximum yield. Significant positive correlation was observed within most of the antinutritional factors, whereas protein possessed negative and significant correlation with phytic acid content. On the other hand, phytic acid exerted a positive and direct effect while C-glycosylflavones had negative effect on grain yield per plant, which could be utilized for further breeding improvement programmes that can contribute to popularity towards increased use of pearl millet.